Acessibilidade urbana e segregação socioespacial: um estudo configuracional da distribuição de renda na cidade de Cascavel (PR) - Andrade, Ana Luisa de (2021)
The Brazilian urbanization process resulted in a movement of expansion and development of cities, which sees a need to understand the relationship between their physical, social and adequate aspects. In this process, the promotion of the economy and society was provided, understanding how the city is essential for its development; with that, as issues segregation, inequality and accessibility to urban resources are considered some of the main social problems suffered. Given this, the issue that instigated this search was: “How does income distribution relate, from a configurational point of view, with urban segregation and spatial accessibility?”. The general objective of the study was to analyze the urban configuration of Cascavel (PR) and its relationship with urban accessibility and socio-spatial segregation, based on the population's income distribution. The methodology used for Space Syntax, through the measures of Global and Local Integration, Connectivity and Choice. The limited results, in terms of Global Integration, that the city has a very integrated central core and, opposite to that, a periphery with less accessibility. Local Integration evidenced a centrality of neighborhoods with roads that are strongly connected to the center, however, with a low cross-relationship between neighborhoods. With regard to connectivity, the city has a very regular urban grid that helps in this measure. As for the Choice, note that the highways that surround the city contribute to the accessibility of the municipalities neighboring the center of Cascavel, however, on the contrary, they hinder the access of the population that lives in the neighborhoods formed by these physical barriers. When compared as measures to the average nominal income of the population, it is shown that a high-income population is located in the highly integrated center, while the segregated periphery is inhabited by a population with lower income. In addition, no similarity was found between segregated neighborhoods for neighborhoods with lower income, since the former are found on the periphery formed by BR-277, while the latter are located in the northeast region, on the periphery of BR-467.